Reivindicación de la ambivalencia teórica: la reciprocidad como concepto clave - Narotzky, Susana (ENDOXA, 2002)
In this introductory paper the author points out several theoretical problems related to the polisemic and ambiguous uses of the concept of reciproty. However the author concludes that this concept can be very operative to explain transfers that are embedded in domains structured by cultural and social relations.